The Preseismic and Postseismic Phases of the ∼700‐km Deep M w7.9 Bonin Islands Earthquake, Japan - Gardonio, B.; Schubnel, A.; Das, S.; Lyon‐Caen, H.; Marsan, D.; Bouchon, M.; Kato, A. (Geophysical research letters, 2020)
The 30 May 2015 M w 7.9 Bonin Islands earthquake, Japan, is one of the largest deep‐focus earthquakes ever recorded. Its occurrence, close to 700‐km depth, in an area without any known historical seismicity, along with its magnitude, was a surprise to scientists. Deep earthquakes are generally believed to have few aftershocks and no foreshocks. Here, we explore the earthquake productivity in the hypocentral surroundings and detect 49 not previously identified earthquakes, 28 of which occurred during an accelerating preseismic phase that started 3 months prior to the main shock. This is the first time that such foreshock activity has been observed for a deep earthquake. The preseismic and postseismic activity suggests transformational faulting within a metastable olivine wedge (MOW) inside the slab at depth as the triggering principal mechanism for this deep earthquake sequence, the seismicity starting where the backward bending of the subducting Pacific plate is maximum. Plain Language Summary Deep earthquakes have been puzzling seismologists for almost a century, since their discovery in the 1920s. Earthquakes deeper than 50 km represent about 25 % of the global seismicity, and deep‐focus earthquakes are defined as those located at 300‐km depth or more. They can be exceedingly large and occur at temperatures and pressures where sliding and fracture are inhibited, thus the brittle fracture/friction mechanism, valid in Earth's crust, cannot hold. Despite their abundance, the physical mechanism behind deep‐focus earthquakes is still a subject of ongoing debate. The Bonin Islands earthquake (30 May 2015, M w7.9) occurred at 680‐km depth in a previously quiet area. In order to better understand why and how it occurred there, we searched for previously unknown earthquakes in the surroundings. For the first time, we identify a preseismic phase preceding such a very deep‐focus earthquake. The location of the newly detected earthquakes reveals the geometry of the slab at depth, and their spatiotemporal distribution supports transformation of metastable olivine as the rupture initiation process. Key Points We present the first evidence of intense foreshock activity before a deep‐focus earthquake 49 newly detected EQs reveal slab geometry and the possible existence of metastable olivine wedge at depth We find a low productivity aftershock sequence that follows Omori's law